2022
DOI: 10.1111/petr.14288
|View full text |Cite
|
Sign up to set email alerts
|

Directly observed therapy to promote medication adherence in adolescent heart transplant recipients

Abstract: Purpose: HT recipients experience high levels of medication non-adherence during adolescence.Thispilotstudyexaminedtheacceptabilityandfeasibilityofanasynchro-nousDOTmHealthapplicationamongadolescentHTrecipients.Theappfacilitates trackingofpatients'dose-by-doseadherenceandenablestransplantteammembers toengagepatients.TheDOTapplicationallowspatientstoself-recordvideoswhile takingtheirmedicationandsubmitforreview.Transplantstaffreviewthevideosand communicate with patients to engage and encourage medication adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 73 publications
(173 reference statements)
0
11
0
Order By: Relevance
“…The volume of and popularity of in-app messaging implies positive perceptions about the 2-way communication and support features of the mHealth app. This finding was further bolstered by the previously reported results of the pilot study 19 that showed patients who completed the 12-week protocol submitted 1211 videos of a possible 1344-demonstrating a 90.1% adherence rate. This adherence rate would have been approximately 82.9% if the videos not submitted by the 2 patients who dropped out from the study prematurely in the third week had been counted.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The volume of and popularity of in-app messaging implies positive perceptions about the 2-way communication and support features of the mHealth app. This finding was further bolstered by the previously reported results of the pilot study 19 that showed patients who completed the 12-week protocol submitted 1211 videos of a possible 1344-demonstrating a 90.1% adherence rate. This adherence rate would have been approximately 82.9% if the videos not submitted by the 2 patients who dropped out from the study prematurely in the third week had been counted.…”
Section: Discussionmentioning
confidence: 66%
“…This mHealth intervention 18,19 was unique because it included features and functionalities that target multiple and modifiable risk factors for nonadherence and promote sustained behavioral change. 9,12,21 Previous studies involving mHealth interventions for pediatric transplant patients have mainly focused on the delivery of notifications as reminders to take medications, often in the form of an alarm on a mobile phone or other smart device.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations